MARKETING STIMULI AND AUTHORS' INTENTIONS TO CHOOSE A PUBLISHER FOR PUBLISHING THEIR BOOKS: THE MEDIATION ROLE OF PERCEIVED USEFULNESS - Rahayu, Elisa Dwi; Anjaningrum, Widiya Dewi (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2024)
The indie publishing industry faces many challenges in the digital era. Therefore, every publisher must be able to find the determining factor in attracting authors to publish their books. This study aims to determine the strength of the impact of marketing stimuli on purchasing intentions mediated by perceived usefulness. A total of 150 participants of the